Pembelajaran Sentra Iman dan Taqwa (IMTAQ) Melalui Smart TV Pada Anak Usia Dini - Ervina; Muzakki; Aghnaita; Neela Afifah (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research is motivated by the Center for Faith and Piety (IMTAQ) learning via Smart TV. The Center for Faith and Piety (IMTAQ) learning model is a learning model in schools by implementing Smart TV in the teaching and learning process for children. On this basis, this research aims to describe the learning of the Center for Faith and Piety (IMTAQ) via Smart TV. The research method used is descriptive qualitative research. The research subjects were one homeroom teacher and one student in the RA Perwanida Kasongan Center for Faith and Taqwa (IMTAQ) class, Central Kalimantan. Data collection methods include observation, interviews and documentation. At the end of the research carried out, the results were obtained that in an effort to implement the Center for Faith and Piety (IMTAQ) learning at RA Perwanida Kasongan via Smart TV with the theme of Islamic learning, the universe and language, it can help children in the learning process, it will involve children more enthusiastically and happily in participating. learning. Apart from that, it also makes it easier for children because they use Smart TV by utilizing digital technology and makes it easier for teachers to provide learning material when conveying it to children.